Violência sexual como um desafio à saúde pública: perfil epidemiológico - Annah Rachel Graciano; Raquel Isaac de Almeida; Luciana Zendron Carneiro (UniEVANGÉLICA, 2018)
Objective: To verify the prevalence of sexual violence in Brazil between 2009 and 2015, according to the general population and to the female and male gender. Methods: An ecological study was conducted, based on sources from the Sistema de Informação de Agravos de Notificação (SINAN) and the Instituto Brasileiro de Geografia e estatística (IBGE). Subsequently, the prevalence rates for the general population and for gender were calculated. Results: The survey showed that the prevalence of sexual violence in Brazil increased between 2009 and 2013, with a general prevalence increase of 300%. The minimum prevalence was in 2015 with prevalence rate (TP) = 0.02 per 100,000 population (95% CI: 0.02 - 0.03), and the highest TP was equivalent to 12.1 (95% CI: 12.0 - 12.3). The female gender had a higher PW than the male gender in all years, reaching a peak prevalence of 20.9 (95% CI: 20.0 - 21.8), while in males the peak was 3.0 (95% CI 2.9 - 3.2). Conclusions: It was concluded that sexual violence is still very prevalent in Brazil despite the decrease in frequency after 2014 and it is still a public health problem. Women are the most frequent victims as evidenced in the study.